Link Between Ferritin, Vitamin D, Performance, and Eating Attitudes in Female Athletes - Tsukahara, Yuka; Torii, Suguru; Taniguchi, Yukiko; Kusakabe, Torao; Murakami, Hideki; Yamasawa, Fumihiro; Akama, Takao (International Journal of Sports Medicine, 2025)
Iron and vitamin D deficiencies can affect athletes’ health and performance. However, the epidemiology and associated risk factors remain unclear. Forty-three elite female athletics athletes (20.2±1.9 years) were included. A survey regarding the training schedule and Eating Attitudes Test-26, body composition, bone mineral density, and serum 25-hydroxyvitamin D (25(OH)D) and ferritin levels were assessed. Mean serum 25(OH)D and ferritin levels were 25.2±5.5 ng/mL and 29.0±13.2 ng/mL, respectively, and 83.7% and 41.9% of athletes had vitamin D and ferritin insufficiency, respectively. Serum 25(OH)D level was negatively correlated with the number of rest days per week (Coefficient,−6.19; 95% confidence interval [CI],−9.82–−2.57; p=0.002), and serum ferritin level was negatively correlated with body mass index (Coefficient,−3.87; 95% CI,−7.57–−0.16; p=0.041). Performance levels were positively correlated with serum vitamin D levels (Coefficients, 7.25; 95% CI, 0.25–14.25; p=0.043) and negatively correlated with EAT-26 scores (Coefficient,−7.30; 95% CI,−12.61–−1.98; p=0.009) and body fat percentage (Coefficient,−13.26; 95% CI,−24.66–−1.86; p=0.025). Vitamin D and ferritin insufficiencies are prevalent among Japanese female athletics athletes. Serum vitamin D level was related to performance level.
Keywords: athletics; anemia; iron-deficiency